Childhood Brain Development, the Educational Achievement Gap, and Cognitive Enhancement - Jotterand, Fabrice (Frontiers in Pharmacology, 2018)
Research on the effects of adversity on the brain of children initially encountered strong skepticism mainly due to the fear of stigmatization and the potential pathologizing of poverty as a disease. Despite initial resistance, an increasing body of work demonstrates a correlation between low socioeconomic status and brain development. This article will focus specifically on the impact of poverty (material, economic, and social) on childhood brain development and educational achievement. Some suggest that the use of cognitive enhancers in healthy students is perfectly acceptable and should be promoted to counterbalance the failure of traditional means to improve educational achievements. In this article, I critically assess the claim that a broad use of cognitive enhancers should be promoted and offer an alternative approach. The first section evaluates the neuroscientific facts and evidence of the impact of poverty on brain development and outlines some of the criticisms raised against the “neuroscience of poverty”. The second section focuses on the proposal made by Keisha Shantel Ray (2016) that promotes the use of cognitive enhancers as a means to address poor educational attainment. I criticize the basis of her argument and propose a different approach I call the clinical ideal. Subsequently I provide some ethical pointers to allow an ethical and prudent use of cognitive enhancers in the educational setting. The main point of the article is not to reject prima facie the use of cognitive enhancers in socially disadvantaged students but rather provide a more nuanced approach.